Cognitive Sequelae of Silent Ischemic Lesions Following Carotid Artery Stenting: Possible Role of Age-Related Moderation - Huang, Kuo-Lun; Ho, Meng-Yang; Chang, Yeu-Jhy; Chang, Chien-Hung; Liu, Chi-Hung; Wu, Hsiu-Chuan; Chang, Ting-Yu; Lee, Tsong-Hai (Frontiers in Aging Neuroscience, 2022)
Background: The occurrence of ischemic lesions is common in patients receiving carotid artery stenting (CAS), and most of them are clinically silent. However, few studies have directly addressed the cognitive sequelae of these procedure-related silent ischemic lesions (SILs). Objective: In this study, we attempted to investigate the effects of SILs on cognition using a comprehensive battery of neuropsychological tests. Method: Eighty-five patients with unilateral carotid stenosis and 25 age-matched healthy volunteers participated in this study. Brain MRI was performed within 1 week before and 1 week after CAS to monitor the occurrence of post-CAS SILs. A comprehensive battery tapping reading ability, verbal and nonverbal memory, visuospatial function, manual dexterity, executive function and processing speed was administered 1 week before and 6 months after CAS. To control for practice effects on repeated cognitive testing, the reliable change index (RCI) derived from the healthy volunteers was used to determine the cognitive changes in patients with carotid stenosis. Results: Among the 85 patients with carotid stenosis, 21 patients received medical treatment (MED group), and procedure-related SILs were noted in 17 patients (SIL+ group) but not observed in 47 patients (SIL- group) after undergoing CAS. Two-way (group x phase) ANOVA revealed that the volunteer group showed improved scores in most cognitive tests while only limited improvement was noted in the SIL- group. The MED and control groups tended to show improvement in the follow-up cognitive testing than the SIL+ group. However, most of the cognitive changes for each patient group did not exceed the upper or lower limits (z=±1.0) of the RCI. Conclusions: Although the occurrence of procedure-related SILs is common in patients undergoing CAS, their impacts on cognitive changes after CAS may be limited. The practice effect should be taken into consideration when interpreting cognitive changes following CAS.